Aplikasi Rizobakteri Pantoea agglomerans untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Jagung (Zea mays, L.) Varietas Hibrida BISI-2 - I GUSTI NGURAH RAKA; KHAMDAN KHALIMI; I DEWA NYOMAN NYANA; I KETUT SIADI (Agrotrop : Journal on Agriculture Science, 2012)
This experiment was conducted in the village of Sibang Gede, District of Abiansemal, BadungRegency on November 2011 until February 2012. The research objective is to enhance the growth andyield of maize hybrid BISI-2 using rhizobacteria Pantoea agglomerans as PGPR in compostformulations. This study used a randomized block design (RBD) single factor with 5 treatments and 5replications. The treatments tested were P. agglomerans BS7a, P. agglomerans BS7b, P. agglomeransBS2a, and P. agglomerans BS5a. All treatments P. agglomerans formulated in the form of compostand given a dose of 50 g/hole. As a control dose of compost 50 g/hole without PGPR. The resultsshowed that the application of rhizobacteria P. agglomerans increased the maximum plant height, netassimilation rate, crop growth rate, chlorophyll content of leaves, fresh weight of roots per plant, ovendried weight of stover per plant, number of seeds per plant, cob length, cob diameter, seed weightmoisture content of 12% per plant and seed yield of 12% water content per hectare.